2016
DOI: 10.1007/jhep06(2016)056
|View full text |Cite
|
Sign up to set email alerts
|

Anderson localization in high temperature QCD: background configuration properties and Dirac eigenmodes

Abstract: Abstract:We investigate the properties of the background gauge field configurations that act as disorder for the Anderson localization mechanism in the Dirac spectrum of QCD at high temperatures. We compute the eigenmodes of the Möbius domain-wall fermion operator on configurations generated for the SU(3) gauge theory with two flavors of fermions, in the temperature range [0.9, 1.9]T c . We identify the source of localization of the eigenmodes with gauge configurations that are self-dual and support negative f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 65 publications
5
68
0
1
Order By: Relevance
“…In this respect it is worth mentioning the results of ref. [11], which support a connection between localised modes and certain topological objects, namely the monopoleinstantons, which might be responsible for the deconfinement transition (see refs. [26][27][28][29] and references therein).…”
Section: Jhep02(2017)055mentioning
confidence: 77%
See 3 more Smart Citations
“…In this respect it is worth mentioning the results of ref. [11], which support a connection between localised modes and certain topological objects, namely the monopoleinstantons, which might be responsible for the deconfinement transition (see refs. [26][27][28][29] and references therein).…”
Section: Jhep02(2017)055mentioning
confidence: 77%
“…Further evidence has been recently obtained in ref. [11], in which a clear correlation is reported between the position of localised modes and that of the favourable "islands" of Polyakov loops. Relating deconfinement and chiral symmetry restoration is more difficult, despite the ample numerical evidence of a close relationship.…”
Section: Jhep02(2017)055mentioning
confidence: 91%
See 2 more Smart Citations
“…Given the close relation between confining and chiral properties of the theory, it is natural to wonder if confinement is somehow responsible for the accumulation of modes near the origin, and analogously if deconfinement causes the depletion of this spectral region. A similar question of course can be asked also for other gauge theories.Adding to the mistery, or possibly helping to solve it, a third phenomenon has been observed to take place in QCD around the critical temperature, namely the localisation of the lowest modes of the Dirac operator [12][13][14][15][16][17][18]. Numerical studies on the lattice have shown that while in the low-temperature phase all the Dirac modes are extended throughout the whole system, above T c the lowest modes get localised [12][13][14][15][16][17][18] on the scale of the inverse temperature [16].…”
mentioning
confidence: 99%